2006
DOI: 10.1590/s1516-635x2006000300010
|View full text |Cite
|
Sign up to set email alerts
|

Initial identification and sensitivity to antimicrobial agents of Salmonella sp.isolated from poultry products in the state of Ceara, Brazil

Abstract: The objective of this research was to isolate and to verify the sensitivity to antimicrobial agents of strains of Salmonella sp. isolated from poultry products in the state of Ceara, Brazil. A total number of 114 samples was collected from 63 broiler carcasses derived from two processing plants and two supermarkets, and 51 excreta samples were collected in broiler farms located in the state of Ceara, which used three live production stages. Each excreta sample consisted of a fresh excreta pool from 100 birds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
2
7
1
5
Order By: Relevance
“…The authors mention that probably the large number of serotypes recognized results from the mixture of a large number of inputs of same rating but from different sources; this probably being the same reason for the difference between the serotypes isolated from this study. In relation to feces, the data of the present study disagree with Oliveira et al (2006), who analyzing samples of feces and carcasses of broilers in the state of Ceará, Brazil observed contamination by Salmonella spp. only in the carcasses.…”
Section: Discussioncontrasting
confidence: 99%
“…The authors mention that probably the large number of serotypes recognized results from the mixture of a large number of inputs of same rating but from different sources; this probably being the same reason for the difference between the serotypes isolated from this study. In relation to feces, the data of the present study disagree with Oliveira et al (2006), who analyzing samples of feces and carcasses of broilers in the state of Ceará, Brazil observed contamination by Salmonella spp. only in the carcasses.…”
Section: Discussioncontrasting
confidence: 99%
“…This is supported by previous data from around the world (Uyttendaele et al, 1998;Dominguez et al, 2002;Goncagü l et al, 2005;Oliveira et al, 2006). The presence of Salmonella Enteritidis in poultry meat is a significant contamination risk, as many authors report that this serovar represents the main source of foodborne diseases (Humphrey and Jørgensen, 2006;Oliveira et al, 2006).…”
Section: Distribution Of Salmonella Serovarssupporting
confidence: 75%
“…According to the Centers for Disease Control and Prevention (CDC) in United States, there are 1.34 million of cases of disease, 16.430 hospitalizations, and 582 deaths each year. The total annual cost resulting from foodborne Salmonella infections is estimated to be approximately $3.5 billion (Oliveira et al, 2006). According to Humphrey and Jørgensen (2006), an estimated 100,000 cases of Salmonella infection in the United Kingdom every year are indicative of much of Western Europe.…”
Section: Introductionmentioning
confidence: 99%
“…The data from the present study indicated that all isolated Salmonella strains exhibited absolute resistance (100%) against amoxicillin/clavulanic acid, indicating the limited therapeutic value of this antibiotic. Of the most common antimicrobial resistance in Salmonella, beta-lactam resistance was cited previously in Pakistan and Brazil [29,30] and can therefore be considered a worldwide problem. This resistance may be attributed to indiscriminate use of antibiotics at recommended doses or at subtherapeutic doses as feed additives to promote growth, and as chemotherapeutic agents to control epizootic diseases on farms.…”
Section: Discussionmentioning
confidence: 99%